(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Findings will inform recommendations for improving social work curricula and bridging the gap between theory and practice in the field. Six instances were chosen at random from three colleges in the North, Central, and South areas of Kerala for the research. The subjects were chosen using a purposive sample strategy in the research. We gathered this information via in-depth interviews. The lack of certification and quality standards was seen by the participants as an issue. Many people still confuse social work with social service since there isn’t an organisation that can speak for the field as a whole.